1961
DOI: 10.1071/ch9610253
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Waxes. XVIII. Beeswax: A Spectroscopic and Gas Chromatographic Examination

Abstract: S m r y A quantitative examination has been made of the components of hydrolysed beeswax.This was achieved by separation into hydrocarbons, monohydric alcohols, " diols ", acids, and hydroxyacids. The alcohol and acid fractions were reduced to the corresponding hydrocarbon mixtures and these together with the naturally occurring hydrocarbons were examined by gas chromatography, which demonstrated their straight-chain character and gave the chain lengths and percentage composition of the components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 5 publications
3
17
1
Order By: Relevance
“…The dominant group of the beeswax hydrocarbons is unbranched alkanes containing from 20 to 35 carbon atoms. These results are in line with those reported by other authors (White et al, 1960;Downing et al,1961;Lorbeer, 1999, 2000;Jimenez et al, 2004;Serra Bonvehi and Ornantes Bermejo, 2012;Maia and Nunes, 2013;Waś et al, 2014). In addition, our studies showed differences in the content of n-alkanes in the beeswax collected from light and dark combs.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The dominant group of the beeswax hydrocarbons is unbranched alkanes containing from 20 to 35 carbon atoms. These results are in line with those reported by other authors (White et al, 1960;Downing et al,1961;Lorbeer, 1999, 2000;Jimenez et al, 2004;Serra Bonvehi and Ornantes Bermejo, 2012;Maia and Nunes, 2013;Waś et al, 2014). In addition, our studies showed differences in the content of n-alkanes in the beeswax collected from light and dark combs.…”
Section: Discussionsupporting
confidence: 82%
“…According to different authors, these aliphatic, long-chain compounds contain from 17 to 35 atoms of carbon (White et al, 1960;Downing et al, 1961;Lorbeer, 1999, 2000;Jimenez et al, 2004;Serra Bonvehi and Ornantes Bermejo, 2012;Maia and Nunes, 2013;Waś et al, 2014). Unbranched saturated hydrocarbons (n-alkanes) comprise about 67% of all the beeswax hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the GC-MS analysis showed that the dominant group of the beeswax hydrocarbons is n-alkanes containing from 20 to 35 carbon atoms in their molecules. These results are in line with those previously reported by other authors, although slightly different lengths of the carbon chains were indicated (White et al, 1960;Downing et al, 1961;Lorbeer, 1999, 2000;Jimenez et al, 2004;Serra Bonvehi and Ornantes Bermejo, 2012). The differences in the qualitative composition of the beeswax reported by different authors are undoubtedly caused by various limits of detection of these compounds and by the manner of beeswax sample preparation for the analysis.…”
Section: Determination Of Beeswax Hydrocarbons By Gc-mssupporting
confidence: 91%
“…The study of the composition of beeswax became possible with the advent of gas chromatography techniques. This method was used for the first time for the analysis of beeswax hydrocarbons by White et al (1960) and Downing et al (1961). Gas chromatography with different kinds of detection (FID, MS) is now commonly used in studies of beeswax composition (Aichholz and Lorbeer, 1996, 1999, 2000Jimenez et al, 2003Jimenez et al, , 2004Jimenez et al, , 2006Jimenez et al, , 2007Jimenez et al, , 2009Serra Bonvehi and Ornantes Bermejo, 2012;Maia and Nunes, 2013), and the majority of compounds belonging to certain homologous series have been characterized.…”
Section: Introductionmentioning
confidence: 99%
“…As it has been previously stated, the indicators of beeswax adulteration with hydrocarbons of an alien origin (e.g. paraffin) can be hydrocarbons containing even numbers of carbon atoms in the molecule (these hydrocarbons occur in trace amounts in beeswax), and the presence of hydrocarbons containing over 35 atoms of carbon, which were not found in beeswax (White, Reader, & Riethof, 1960;Downing et al, 1961;Streibl, Stransky, & Sorm, 1966;Tulloch & Hoffman, 1972;Tulloch, 1973;Jimenez et al, 2004Jimenez et al, , 2006Jimenez et al, , 2007Jimenez et al, , 2009Serra Bonvehi & Ornantes Bermejo, 2012). The addition of paraffin results in an increase in the hydrocarbon content.…”
mentioning
confidence: 99%